1993
DOI: 10.1007/bf01458030
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of poly-(R)-3-hydroxyalkanoate: An emulsion polymerization

Abstract: Poly-(R)-3-hydroxyalkanoates (PHAs) are bacterial storage polyesters, which are accumulated by a wide variety of microorganisms as a reserve of carbon and energy. Currently, these biopolymers are receiving much attention because of their potential application as biodegradable and biocompatible plastics. The polymer appears as submicron intracellular granules. The biosynthesis of these granules has been studied extensively but many observations remain inexplicable. This paper draws an analogy between the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…PHA inclusions appear to have a single boundary layer, which was first believed to be a membrane 15 to 20 nm in thickness or a homogenous layer of PhaC (42,88,92). Later reports described the inclusions to be surrounded by a PL monolayer with a 4-nm width and with proteins engaged in PHA synthesis, mobilization, and structural function embedded (38,61,93). In R. eutropha, four classes of proteins have been demonstrated to occur at the surface of PHA inclusions: PhaC; PhaZ; a transcriptional repressor, PhaR; and phasins (PhaP).…”
Section: Vol 187 2005mentioning
confidence: 99%
“…PHA inclusions appear to have a single boundary layer, which was first believed to be a membrane 15 to 20 nm in thickness or a homogenous layer of PhaC (42,88,92). Later reports described the inclusions to be surrounded by a PL monolayer with a 4-nm width and with proteins engaged in PHA synthesis, mobilization, and structural function embedded (38,61,93). In R. eutropha, four classes of proteins have been demonstrated to occur at the surface of PHA inclusions: PhaC; PhaZ; a transcriptional repressor, PhaR; and phasins (PhaP).…”
Section: Vol 187 2005mentioning
confidence: 99%
“…Recently, it has been suggested that this simply results from the slow nucleation kinetics of small PHA par- NARD andSANDERS, 1988, 1989; KAWAGU-ticles. For a typical poly(3HB) granule exhibiting a diameter of 0.5 mm, the time to nucleate for crystallization is approximately 30,000 years (DE KONING and MAXWELL, 1993). A much shorter crystallization period can be induced by compaction of the granules by centrifugation, perturbation by sonication, damage of the surrounding membrane by exposure of the granules to solvents, sodium hydrochlorite or to hydrolytic enzymes, or by freezing and thawing cycles (BARNARD and SANDERS, 1989;DE KONING and MAXWELL, 1993).…”
Section: Function Of Phamentioning
confidence: 99%
“…eutropha H16 has not yet been identified. However, PHB granules, as well as TAG inclusions, possess a hydrophobic core of the polyester or lipid, respectively, which is thought to be surrounded by a monolayer of phospholipids (de Koning & Maxwell, 1993;Hocking & Marchessault, 1994;Mayer & Hoppert, 1997;Wältermann et al, 2005). This common structure allows the targeting of PhaP1 to PHB granules and also TAG inclusions, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%